Ovarian huge serous cystadenoma with torsion in adolescent girl: a case report - Khade, Shweta Avinash; Shirodkar, Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
In adolescent Ovarian cysts are an extremely common gynaecological problem. Majority of ovarian cysts are benign with few cases being malignant. Ovarian serous cystadenomas are rare in children. A 14-year-old presented with severe abdominal pain and abdominal distention. She underwent emergency laparotomy and surgical removal, the mass was found to be torsion of ovarian serous cystadenoma-fibroma on histology. In conclusions, germ cell tumours the most important causes for the giant ovarian masses in children. Epithelial tumours should not be forgotten in the differential diagnosis.